A Short Peptide of Autotransporter Ata Is a Promising Protective Antigen for Vaccination Against Acinetobacter baumannii - Sun, Peng; Li, Xin; Pan, Chao; Liu, Zhicheng; Wu, Jun; Wang, Hengliang; Zhu, Li (Frontiers in Immunology, 2022)
With the emergence of multidrug-resistant strains, Acinetobacter baumannii infection is becoming a thorny health problem in hospitals. However, there are no licensed vaccines against A. baumannii. Acinetobacter trimeric autotransporter (Ata) is an important known virulence factor located on the outer membrane of bacteria. Herein, we carried out a series of experiments to test the immunogenicity of a short C-terminal extracellular region of Ata (Ataα, only containing 39 amino acids) in a murine model. The short peptide Ataα was fused with the cholera toxin B subunit (CTB), which has been reported to have immunoadjuvant activity. The fusion protein showed no inflammation and organ damages, and have the ability to elicit both Th1 and Th2 immune responses in mice. The bactericidal activities against A. baumannii and prophylactic effects of the fusion protein were further evidenced by a significant reduction in the bacterial load in the organs and blood. In addition, the candidate vaccine could provide broad protection against lethal challenges with a variety of A. baumannii strains. Moreover, when CpG was added on the basis of aluminum adjuvant, the immune response, especially cellular immunity, could be further strengthened. Overall, these results revealed that the Ataα is a promising vaccine target against A. baumannii infection.